GAMBARAN PELAYANAN FARMASI KLINIK DI APOTEK WILAYAH KOTA TANGERANG SELATAN CLINICAL PHARMACY SERVICE AT COMMUNITY PHARMACY IN SOUTH TANGERANG REGENCY - Apriansyah, Ahmad (STIKes Bakti Tunas Husada, 2018)
Background : Giving the drug information and counceling are parts of pharmacist clinical task as be stated in ministry of health statue number 35 year 2014 on Pharmacy service standar in community pharmacy (Permenkes no 35 tahun 2017 tentang standar pelayanan kefarmasian di apotek). Through these tasks, pharmacist can inprove the patient therapy outcome. Aim : The purpose o this study was to describe the clinical service of Â drug information in community pharmacies (CP) at South Tangerang City. Methods : This was a descriptive-explorative study with survey technic. Sample were the 50 CPs and clinical pharmacy services were evaluated on their pharmacist who could be met at the visiting time. Results & Conclusion : Thirty eight percent of pharmacists could be met at the visiting time. The highest percentage of drug information service is drug usage (72,22%) whereas the lowest are drug interaction and the way of its prevention i.e 5,55%. Â The quality of pharmacy clinical service of drug information is 41,66% and meet the bad criteria. The clinical pharmacy service of drug information in south Tangerang has not been run well and met the Pharmacy service standard yet.Â Keywords: drug information service, pharmacit, south tangerang, community pharmacy.